1998
DOI: 10.1093/humrep/13.3.709
|View full text |Cite
|
Sign up to set email alerts
|

Ooplasmic injection of elongating spermatids for the treatment of non- obstructive azoospermia

Abstract: We applied the technique of ooplasmic elongating spermatid injection to the treatment of non-obstructive azoospermia. Mature oocytes were injected with elongating spermatids isolated from testicular biopsy material obtained from 13 non-obstructed azoospermic men. Seventy-three oocytes were successfully injected with elongating spermatids and were then cultured for 36 h. At 13 h post-injection 68 oocytes were found to be activated and 52 of them were fertilized. Forty-one 2- to 4-cell stage embryos developed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 34 publications
0
43
0
1
Order By: Relevance
“…After optimization of the isolation procedure, the focus was on finding the optimal conditions for culturing the cells. The medium constituents were chosen from a literature review of previously published data on factors affecting viability of germ cells (Jutte et al, 1981; Caussanel et al, 1996; Sofikitis et al, 1998; Pentikäinen et al, 2000; Tesarik et al, 2002; Peterson and Soder, 2006; Oatley et al, 2007). For instance, lactate was added as the primary energy source for spermatids, along with factors secreted by Sertoli cells that have been shown to play an important role in maintaining viability of meiotic and post‐meiotic germ cells (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…After optimization of the isolation procedure, the focus was on finding the optimal conditions for culturing the cells. The medium constituents were chosen from a literature review of previously published data on factors affecting viability of germ cells (Jutte et al, 1981; Caussanel et al, 1996; Sofikitis et al, 1998; Pentikäinen et al, 2000; Tesarik et al, 2002; Peterson and Soder, 2006; Oatley et al, 2007). For instance, lactate was added as the primary energy source for spermatids, along with factors secreted by Sertoli cells that have been shown to play an important role in maintaining viability of meiotic and post‐meiotic germ cells (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, it has also been shown that normal embryo development could be obtained from a sterile mouse strain after ROSI (Sasagawa et al, 1998). In addition, in the human, babies have been delivered from round and elongated spermatids (Fishel et al, 1995(Fishel et al, , 1997Mansour et al, 1996;Tesarik and Mendoza, 1996a;Tesarik et al, 1996b;Antinori., 1997;Araki et al, 1997;Vanderwalmen et al, 1997;Barak et al, 1998, Bernabeu et al, 1998Sofikitis et al, 1998), but the efficacy of the process is not yet established. Although the underlying mechanism of this technique is not fully understood, the fact that fertilization, implantation, and birth of healthy infants can occur after the injection of spermatids into oocytes has led us to use this technique for infertile couples in those cases in which the technique represented their only chance of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Intact round spermatid injection (ROSI) has resulted in the delivery of healthy infants (Tesarik and Mendoza, 1996a;Tesarik et al, 1996b;Vanderzwalmen et al, 1997;Barak et al, 1998;Bernabeu et al, 1998), as has treatment with elongated spermatid injection (ELSI) (Fishel et al, 1995(Fishel et al, , 1997Mansour et al, 1996;Antinori, 1997;Araki et al, 1997;Vanderzwalmen et al, 1997;Sofikitis et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…One might consider using iPS cell-derived spermatids in the clinical setting. However, although oocytes have been fertilized with elongated spermatids [39,40], they were insufficiently fertilized with premature, round spermatids, resulting in poor embryonic development [41,42,43]. Successful fertilization of oocytes with more matured male germ cells in vitro needs to be examined in preclinical research.…”
Section: The Induction Of Germ Cells From Ips Cellsmentioning
confidence: 99%